Passport Checks: Interactions Between Matching Faces and Biographical Details. Issue 6 (11th October 2016) - McCaffery, Jennifer M.; Burton, A. Mike
Summary: Matching unfamiliar faces is known to be a difficult task. However, most research has tested viewers' ability to match pairs of faces presented in isolation. In real settings, professionals are commonly required to examine photo ID that contains other biographical information too. In three experiments, we present faces embedded in passport frames and ask viewers to make face matching decisions and to check biographical information. We find that the inclusion of a passport frame reduces viewers' ability to detect a face mismatch. Furthermore, the nature of the face match influences biographical data checking—true matches lead to fewer detections of invalid data. In general, viewers were poor at spotting errors in biographical information. This pattern suggests that detection of fraudulent photo ID is even harder than current experimental studies suggest. Possible mechanisms for these effects are discussed. Copyright © 2016 John Wiley & Sons, Ltd.